Nutrition Students’ Experiences of Interprofessional Learning in a Nursing Home - Heyerdahl, Ella; Ottesen, Marte; Molin, Marianne; Hestevik, Christine Hillestad; Sørlie, Venke Marion; Sellevold, Gerd Sylvi (Journal of Research in Interprofessional Practice and Education, 2020)
Background: Interprofessional experience is vitally important for nutrition students, as nutritionists often find themselves working independently in a team with other professionals. Few studies have explored qualitatively how nutrition students perceive learning activities in an interprofessional setting.Methods and Findings: Third-year bachelor’s degree nutrition students participated in a focus group interview after interprofessional learning in a nursing home. A qualitative study with a phenomenological-hermeneutical approach was conducted to investigate lived experiences. One theme emerged from the data analysis: A professional understanding of oneself and others. Being acknowledged as a professional, being an active participant, and collaborating to enhance resident care were revealed as sub-themes.Conclusions: A short period of interprofessional learning in an authentic setting may expand students’ experiences and enhance professional confidence.